1999
DOI: 10.1143/jjap.38.3482
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Oxygen Plasma Resistance of Low-k Methylsilsesquioxane by H2 Plasma Treatment

Abstract: The visco-plastic model developed in part I of this work is used here to study the dislocation evolution in high pressure Czochralski growth of InP single crystals. Towards this an in-house computational fluid dynamics code MASTRAPP is linked to the ABAQUS software. MASTRAPP has the capability to predict the thermal field history in the Czochralski furnace throughout the growth period. The thermal loading history determined through MASTRAPP is fed to ABAQUS and the visco-plastic constitutive equations are inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…It is thought that high contents of Si-O bond that has high thermochemical energy [10] in the low-k SiCOH films can contribute to decrease of leakage current pass. Furthermore, the H 2 plasma treatment can provide hydrogen radicals to passivate the surface and bulk of porous films and reduce the defect content [6], which can help reducing leakage current.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thought that high contents of Si-O bond that has high thermochemical energy [10] in the low-k SiCOH films can contribute to decrease of leakage current pass. Furthermore, the H 2 plasma treatment can provide hydrogen radicals to passivate the surface and bulk of porous films and reduce the defect content [6], which can help reducing leakage current.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of hydrogen treatment on the dielectric constant reducing was observed and explained in Refs. [6,7], where it was suggested that hydrogen plasma could enhance the thermal stability and increase the porosity of the films, resulting in lower k values. The He/H 2 plasma induced smaller amount of shrinkage on the film compared to oxygen, nitrogen, ammonia, etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSZ, whose dielectric constant is ∼ 2.6, is methyl-silsesquioxane (MSQ)-Thin Solid Films 515 (2006) 1117 -1120 www.elsevier.com/locate/tsf like structure derived from methyl-silsesquioxane. It has high transmittance in the range of visible light, good planarization properties and good electrical properties [8,9]. The thickness of MSZ could be controlled by tuning the speed of spin coater.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dielectric properties of this nanoporous material are seriously degraded during photoresist removal-an important microelectronic fabrication step that involves O 2 ashing/etching. 6,7 This process also removes the hydrophobic CH x groups from exposed surfaces ͑pore surface as well͒ of the film and allowing the formation of silanol ͑Si-OH͒ groups. As a result, the hydrophillic Si-OH enhances physical adsorption of moisture upon air exposure and increases the dielectric constant.…”
mentioning
confidence: 99%